Effects of Yoga Nidra on Physical, Mental, and Emotional Health Outcomes: A Systematic Review of Randomized Controlled Trials - Giridharan, Selvaraj; Pandiyan, Bhuvana; Godbole, Mrunmai (International Research Journal of Ayurveda & Yoga, 2025)
Background: Yoga Nidra, a guided relaxation practice that originated in ancient Indian traditions, facilitates profound relaxation while maintaining awareness. Despite increasing interest in its benefits for physical, mental, and emotional health, previous reviews have often incorporated combined interventions, thereby diluting evidence regarding its standalone effects. This systematic review synthesized randomized controlled trials (RCTs) evaluating isolated Yoga Nidra to address these gaps. Materials and Methods: A systematic search was conducted across databases, including PubMed, Embase, Cochrane, Scopus, Web of Science, and PsycINFO, from inception to April 2025. Eligible RCTs included adults with health conditions, standalone Yoga Nidra interventions, and comparators. Two reviewers screened the studies, extracted data, and assessed bias using RoB 2. A narrative synthesis outlined the physical, mental, and emotional outcomes, while heterogeneity precluded a meta-analysis. Subgroup/sensitivity analyses and GRADE certainty ratings were also performed. Results: Fifteen RCTs were included to address hypertension, stress, insomnia, and menstrual disorders. The physical benefits included reductions in blood pressure and improvements in heart rate variability in 10 studies. The mental outcomes indicated a decrease in anxiety and depression in 11 studies. Emotional enhancement was observed in six studies. No adverse events were reported; RoB was low in four studies, with some concerns in 11. Conclusion: This systematic review demonstrated that Yoga Nidra exerts a positive influence on physical, mental, and emotional health, with a particular emphasis on reducing anxiety. Despite the limitations posed by study heterogeneity, Yoga Nidra has emerged as a promising evidence-based approach to health promotion. Rigorous and diverse RCTs are necessary to confirm long-term effects and expand the application of integrative care.